Β‐Cell replacement as a treatment for type 1 diabetes: an overview of possible cell sources and current axes of research. (September 2016) - Vieira, A.; Courtney, M.; Druelle, N.; Avolio, F.; Napolitano, T.; Hadzic, B.; Navarro‐Sanz, S.; Ben‐Othman, N.; Collombat, P.
Abstract : To efficiently treat type 1 diabetes, exogenous insulin injections currently represent the main approach to counter chronic hyperglycaemia. Unfortunately, such a therapeutic approach does not allow for perfectly maintained glucose homeostasis and, in time, cardiovascular complications may arise. Therefore, seeking alternative/improved treatments has become a major health concern as an increasing proportion of type 2 diabetes patients also require insulin supplementation. Towards this goal, numerous laboratories have focused their research on β‐cell replacement therapies. Herein, we will review the current state of this research area and describe the cell sources that could potentially be used to replenish the depleted β‐cell mass in diabetic patients.